2019
DOI: 10.20961/desa-kota.v1i2.14762.130-142
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Perkembangan Pariwisata Pantai Di Kabupaten Purworejo

Abstract: Kabupaten Purworejo memiliki pantai yang dijadikan sebagai destinasi wisata yaitu Pantai Jatimalang, Pantai Keburuhan dan Pantai Ketawang Indah dan ditetapkan sebagai desa wisata. Saat ini belum terlihat adanya perkembangan yang berarti seperti belum terpenuhinya elemen-elemen yang harus ada pada pariwisata pantai. Penelitian ini bertujuan untuk mengetahui faktor apa saja yang mempengaruhi perkembangan pariwisata pantai di Kabupaten Purworejo. Pada penelitian ini menggunakan pendekatan deduktif serta metode pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…From the results of the hierarchical process analysis regarding priority strategies to improve Natural Tourism Development in Cirebon Regency and Banyumas Regency as a whole, it is known that the aspects of Facilities and Infrastructure, as well as aspects of increasing the Attraction of Tourist Attractions, are the core of the priority of developing Nature Tourism both in Cirebon Regency and in Banyumas Regency. The results of this analysis are in line with research conducted by Satryanto & Pamungkas (2015) which said that the attractiveness of tourist objects can enhance the development of natural tourism, and research by Febrianingrum et al (2019) and Waseza (2017) which stated that the accessibility criteria were in the form of transportation to tourist objects and road conditions are closely related to the affordability/ease of tourists in reaching tourist sites. If a tourist attraction is not supported by supporting accessibility, tourists also tend not to be interested in visiting tourist objects.…”
Section: Results and Discussion Analytic Hierarchy Process (Ahp)supporting
confidence: 85%
“…From the results of the hierarchical process analysis regarding priority strategies to improve Natural Tourism Development in Cirebon Regency and Banyumas Regency as a whole, it is known that the aspects of Facilities and Infrastructure, as well as aspects of increasing the Attraction of Tourist Attractions, are the core of the priority of developing Nature Tourism both in Cirebon Regency and in Banyumas Regency. The results of this analysis are in line with research conducted by Satryanto & Pamungkas (2015) which said that the attractiveness of tourist objects can enhance the development of natural tourism, and research by Febrianingrum et al (2019) and Waseza (2017) which stated that the accessibility criteria were in the form of transportation to tourist objects and road conditions are closely related to the affordability/ease of tourists in reaching tourist sites. If a tourist attraction is not supported by supporting accessibility, tourists also tend not to be interested in visiting tourist objects.…”
Section: Results and Discussion Analytic Hierarchy Process (Ahp)supporting
confidence: 85%
“…The driving factors for tourism development are freedom of movement, completeness of transportation and communication facilities, accommodation facilities, the attractiveness of tourist areas, and adequate services. Thus, it can be concluded that the supporting factors for development revitalization are adequate facilities and infrastructure (Febrianingrum, Miladan, and Mukaromah 2019).…”
Section: Results and Discussion The Urgency Of Development Revitaliza...mentioning
confidence: 99%
“…Beberapa tahun terakhir pariwisata menjadi salah satu kebutuhan masyarakat untuk berekreasi serta menenangkan diri. Menurut Spillane, terdapat elemen-elemen yang harus dipenuhi oleh suatu destinasi wisata, yaitu atraksi, fasilitas, infrastruktur, transportasi, dan keramahtamahan (Febrianingrum, Miladan, & Mukaromah, 2019). Salah satu destinasi wisata yang sering dikunjungi wisatawan adalah wisata alam.…”
Section: Pendahuluanunclassified